Examining evidence for care in the archaeological record, with specific reference to the Neolithic - Knighton, Paul (2022)
The impact of contemporary urbanisation on health has been studied extensively but the study into to the origin and influences of care during prehistoric periods has created debate among scholars. This paper uses the bioarchaeology of care to explore the presence of care in Neolithic Europe and analyses the relationship between the adoption of a sedentary lifestyle that utilises agriculture and pastoralism and the advancements of health-related caregiving such as new medicines and surgeries. Studies have argued that kinship plays a significant role in determining the provision of care and supports why individuals in a subsistence economy expended the time and resources to prolong an individual’s life. I also use a case study from three Neolithic Linearbandkeramik (LBK) sites in Central Germany to demonstrate how the poor nutrition obtained from the change in dietary patterns, has also been linked to a reduced immune system and in turn, makes individuals more prone to infections. The Index of Care is applied to three case studies of varying pathologies and quantity of skeletal remains: Neolithic amputation (Burial 416 at Buthiers-Boulancourt, France); skeletal dysplasia (Burial 9 at Schweizersbild, Switzerland); Neolithic trepanation (Eira Pedrinha). The application of the Index of Care in this paper shows both the strengths and weaknesses of the program. The Index of Care provides a universal methodology for the determination of care provision in human remains but can only be accurately applied to articulated remains. The case study of Neolithic trepanation from Eira Pedrinha proves this.